2014
DOI: 10.1155/2014/653056
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Molecular Diagnostic Procedure for Applications in Surveillance and Subtyping of Avian Influenza Virus

Abstract: Introduction. The following complete molecular diagnostic procedure we developed, based on real-time quantitative PCR and traditional PCR, is effective for avian influenza surveillance, virus subtyping, and viral genome sequencing. Method. This study provides a specific and sensitive step-by-step procedure for efficient avian influenza identification of 16 hemagglutinin and 9 neuraminidase avian influenza subtypes. Result and Conclusion. This diagnostic procedure may prove exceedingly useful for virological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Alternative molecular methods based on PCR and RT-PCR are more sensitive but need extracted genetic material and require the use of equipment which is available only in diagnostic or scientific laboratories. In consequence, on-site detection of avian influenza viruses is rare until now for both early diagnostics and monitoring [ 32 34 ]. Similarly, a variety of different serological tests that detect the response of the infected host are established but they are not adapted to strains which have a pandemic potential.…”
Section: Detection Of Avian Influenza Virusesmentioning
confidence: 99%
“…Alternative molecular methods based on PCR and RT-PCR are more sensitive but need extracted genetic material and require the use of equipment which is available only in diagnostic or scientific laboratories. In consequence, on-site detection of avian influenza viruses is rare until now for both early diagnostics and monitoring [ 32 34 ]. Similarly, a variety of different serological tests that detect the response of the infected host are established but they are not adapted to strains which have a pandemic potential.…”
Section: Detection Of Avian Influenza Virusesmentioning
confidence: 99%
“…A one-step RT-PCR reaction mixture was prepared using a Takara Prime-Script High Fidelity RT-PCR Kit (Takara Bio, Inc., Shiga, Japan). One-step RT-PCR was conducted with a Gene Amp PCR System 9700 (Applied Biosystems, Waltham, Massachusetts, USA) using the following conditions: one cycle of 42 C for 30 min and 94 C for 2 min; 40 cycles of 98 C for 10 s, 30 C for 30 s, and 72 C for 7 min; one cycle of 72 C for 7 min, and a holding step at 4 C. The reaction mixtures were diluted 1:50 in tris-ethylenediaminetetraacetic acid buffer and the diluted PCR reaction mixtures were prepared using KOD-Plus-Ver.2 (Toyobo Life Science, Tokyo, Japan) and used for PCR amplifications of the HA and NA using the reported primer sets (Tseng et al 2014). We conducted PCR amplifications with a Gene Amp PCR System 9700 (Applied Biosystems) using the following conditions: 94 C for 2 min; 35 cycles of 98 C for 10 s, 50 C for 30 s, and 68 C for 2 min, followed by a hold step at 4 C. The PCR products were purified with the QIAquick PCR Purification Kit (Qiagen) and direct sequencing was performed using the BigDyet Terminator v3.1 cycle sequencing kit (Applied Biosystems) and the 3130 Genetic Analyzer (Applied Biosystems).…”
mentioning
confidence: 99%
“…This method may underrepresent AIV subtype diversity in MWBs due to the low success rate of VI (Runstadler et al, 2007). Some recent studies have suggested that PCR is a better tool for the surveillance of various AIVs circulating in MWBs (Tseng et al, 2014;.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for each of the 16 HA genes were adopted from previous reports by others (Hoffmann et al, 2016;Tseng et al, 2014; or designed in-house when needed. Primer information is summarized in Table 2.…”
Section: Primer Designmentioning
confidence: 99%
See 1 more Smart Citation